2016
DOI: 10.1007/s13197-016-2298-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Maillard reaction evolution, prebiotic carbohydrates, antioxidant activity and α-amylase inhibition in pulse flours

Abstract: In this paper, the quality of bean, chickpea, fava beans, lentil and pea flours from Algeria has been evaluated. Maillard reaction (MR) indicators, modifications in the carbohydrate and protein fractions, antioxidant activity and a-amylase inhibitor of raw, toasted and stored samples were evaluated. Fava beans, beans and peas showed higher content of raffinose family oligosaccharides while chickpeas and lentils showed higher polyol content. Toasting and storage caused slightly change in pulse quality; MR showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
(49 reference statements)
0
17
0
1
Order By: Relevance
“…López-Amorós et al (2006) reported that peas and beans undergo a significant increase in antioxidant activity after germination due to changes in their phenolic composition. Similarly, Moussou et al (2016) reported an increase in antioxidant activities of different pulse flours with toasting. Amarowicz and Pegg (2008) reviewed antioxidant activity and radical scavenging capacity of pulses.…”
Section: Antioxidant Activitymentioning
confidence: 83%
See 1 more Smart Citation
“…López-Amorós et al (2006) reported that peas and beans undergo a significant increase in antioxidant activity after germination due to changes in their phenolic composition. Similarly, Moussou et al (2016) reported an increase in antioxidant activities of different pulse flours with toasting. Amarowicz and Pegg (2008) reviewed antioxidant activity and radical scavenging capacity of pulses.…”
Section: Antioxidant Activitymentioning
confidence: 83%
“…Raffinose (trisaccharide), stachyose (tetrasaccharide) and verbascose (pentasaccharide) are predominant a-galactosides present in pulses. Moussou et al (2016) reported that lentils have the lowest content of raffinose family with 37.5 mg/g DW compared to faba beans (52 mg/g DW), beans (60.9 mg/g DW) and peas (66.3 mg/g DW). They also reported that cotyledons had higher content of these oligosaccharides than seed coats.…”
Section: Oligosaccharidesmentioning
confidence: 99%
“…The α‐amylase activity inhibition was analyzed according to the procedure reported by Moussou et al. (2017). 100 µl of the cookie powder extract was mixed with 100 µl of 2 U/ml α‐amylase solution in a test tube and reacted for 15 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…5) L-(+)-Bornesitol is a methyl myo-inositol found in several plant species. 6) It has been identified by gas chromatography in decaffeinated and non-decaffeinated coffee beverages, 7) chickpeas, lentils, 8) and legumes such as carob beans 9) and grass peas. 10) Bornesitol has also been reported as responsible for the sweet taste of Drypetes floribunda stem and Sapindus rarak pericarp.…”
Section: Introductionmentioning
confidence: 99%